Fiber reinforced direct composite for endodontic treated tooth in one year follow-up - Satrio, Fajar; Mulyawati, Ema; Rinastiti, Margareta (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
After root canal treatment, tooth will be more fragile due to loss of tooth structure integrity as a result of the caries process, access preparation, reduced water, and or tooth fracture. This is the main consideration for determining the material and restoration technique for endodontic treated tooth (ETT). Fiber reinforcement direct composite can maintain the remaining tooth structure and increase fracture resistance. This case report aims to evaluate the 1-year follow-up of fiber reinforcement direct composite in molar tooth after root canal treatment. The first case was a 28-year-old man, who came to RSGM to maintain his left lower right molar which had been filled for about 10 years. On the radiograph, there was a radiopaque filling to the pulp and apical radiolucency. The results of clinical examination obtained previously initiated therapy, asymptomatic apical periodontitis. The second case, a 27-year-old woman, complained pain on biting in the lower left molar for a week. On the radiograph, there was a radiopaque filling at the occlusal side, a non-hermetic obturation material in the root canals, and apical radiolucency. From the clinical examination, previously treated, symptomatic apical periodontitis was obtained. One-visit endodontic treatment was given followed by a direct restoration with composite resin, short-fiber filler, and fiber ribbond. The endodontic treated tooth restored with fiber reinforcement direct composite obtained good results after 1 year follow-up.